Barriers to Online Learning in Mathematics Subjects for MI Muhammadiyah Krendetan Students during the Covid-19 Pandemic - Nisa, Khoirun; Ramadhani, Ineke; Shalikhah, Norma Dewi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
When learning is transferred online, as many as 61% of students feel lazy to take part in learning, especially in mathematics. This study aims to analyze the obstacles experienced by students when learning mathematics online during the Covid-19 pandemic. The method used is descriptive with a quantitative approach. The data collection technique used an instrument in the form of a questionnaire through a google form for students. This research was carried out at MI Muhammadiyah Krendetan by involving 18 grade 6 students. The results showed that there were several obstacles for grade 6 students at MI Muhammadiyah Krendetan, namely online mathematics learning did not take place effectively, only a few students had adequate facilities for support online learning, unstable internet access, and students feel bored. In conclusion, teachers must make efforts to make online mathematics learning during the COVID-19 pandemic interesting, more creative, and innovative and the role of parents and the environment around students to support students' online learning so that mathematics learning can take place optimally.